New Data on the Architectural Works of Non-Muslims From Safranbolu - Gur, Durmus (Fırat University, 2025)
Safranbolu, a district of Karabük in the northwestern Black Sea region, is known for its long period of peaceful coexistence between Orthodox Christians and Turkish Muslims. Following the migration of the non-Muslim population of Safranbolu to Greece in 1923-1924, the cultural artefacts they left behind have been altered or disappeared over time. Apart from the small art objects in the collection of the Benaki Museum in Athens, Greece, new data on the population that migrated from Kıranköy offer significant insights into their life in Safranbolu, including their civil, social, religious and economic structures. Literature reviews, archival research, fieldwork and quantitative data reveal many previously unknown aspects of the non-Muslim population of Safranbolu. Within the framework of this study, research has focused on two regions, Yazıköy and Kıranköy, where the Greek Orthodox population of Safranbolu predominantly resided, and the social, cultural and economic production habits that the people of these regions have maintained for centuries have been examined. Consequently, this study examines prayer rooms/fireplaces, hearths and ovens, workshops/winery (şarapbana), must houses, cisterns, cellars, a mortar with a cross, fountains, terracotta jugs and pithoi used in the production of wine and vinegar, wooden barrels and a winery belonging to the non-Muslim population of Safranbolu that have survived to the present day but have not been historically addressed.

Kuzeybatı Karadeniz’de bulunan Karabük’ün ilçelerinden biri olan Safranbolu’da Hıristiyan Ortodokslarla Türk Müslümanların uzun süre bir arada huzurla yaşadıkları bilinmektedir. 1923-1924 yıllarına kadar Safranbolu’da yaşayan Gayrimüslimlerin Yunanistan’a göç etmeleriyle geride bıraktıkları kültürel miras eserleri zamanla değişime uğramış ya da yok olmuştur. Yunanistan Atina Benaki Müzesi’nin koleksiyonunda yer alan küçük ek sanatları dışında Kıranköy’den Yunanistan’a göç eden halka ait yeni veriler, Safranbolu’daki yaşam süreci, sivil, sosyal, dini ve ekonomik yapıları hakkında önemli bilgiler sunmaktadır. Literatür incelemeleri, arşiv araştırmaları, saha araştırmaları ve nicel veriler, Safranbolulu Gayrimüslimlere dair günümüze kadar bilinmeyen birçok hususu gözler önüne sürmektedir. Çalışma kapsamında Yazıköy ve Kıranköy olmak üzere Safranbolulu Rumların çoğunlukla yaşam sürdükleri iki bölge üzerinde çalışmalar yoğunlaştırılmış, buradaki halkın yüzyıllardır devam ettirdikleri sosyal, kültürel ve okonomik üretim alışkanlıkları incelenmiştir. Bunun sonucunda Safranbolu’da Gayrimüslimlere ait günümüze kadar ulaşmış fakat tarihsel süreçte ele alınmamış olan dua odaları/yangın odaları, şırahaneler/şarapbanalar, sarnıçlar, mahzenler, haç tasvirli dibek taşı, çeşmeler, şarap ve sirke yapımında kullanılan pithoslar, ahşap fıçılar ile şarap fabrikası çalışma kapsamında incelenmiştir.
Safranbolulu Gayrimüslimlerin Mimari Eserlerine Ait Yeni Veriler
Keywords: History of The Byzantine; Bizans Tarihi